With a good heart : a walk from LA to Brooklyn - Griffen, Tom (Tom Griffen, 2020)
"Twenty-five years after an epiphany in a barbershop, Tom Griffen finally began his walk across America. Lugging a heavy backpack and wearing a fresh pair of running shoes, Tom urgently dipped his hands into the Pacific Ocean, bid farewell to loved ones, then began an eastbound journey toward the opposite coast. Tom's reasons for walking were largely unclear, but he was sure of one thing- he couldn't wait for the chance to tell people he had walked all the way across the continent. Tom's plans, however, were thwarted by a mysterious, sidelining injury that spiraled him into an abyss of self-doubt. As he desperately awaited recovery, he considered scrapping the whole ordeal. Then one day he recalled an interaction with a man he met weeks earlier at a California crosswalk. This memory inspired Tom to dig deeper into his true motivation to cross America afoot. What he discovered changed everything, including how he'd approach the second half of his life. With a Good Heart details Tom's journey from coast to coast- a long walk unexpectedly rich in kindness, human togetherness, and ultimately, honest self-acceptance."-- back cover